HAk ASASI MANUSIA DAN SHALAT (Studi Upaya Penegakan keadilan Gender kaum Perempuan dalam Shalat) - Asnawi, Habib Shulton (Sunan Kalijaga State Islamic University & The Asia Foundation, 2011)
The Quran laid down a normative standard, that men and women shouldÂ be held in equal regards, also in matters spiritual. It strives for a meritocracy that the worship of God should be without a spiritual monopoly by one gender. Regrettably, this message becomes distorted through the imposition cultural and sociological aspects. Our patriarchal culture for example, takes the Quran and hadiths at face value, and refusing to realize its underlying message, creates misogynic rules and perspectives. A product thereof is a ban (or at least a strong discouragement) on women from going to the mosques to pray, resulting in a loss of religious rights and a limitation in the avenues of worship for women. Such inequality causes discomfort and loss of rights and dignity to women as human beings, and such inequality, being inherently detrimental towards justice and humanity must be put to an end.